Using Invisible Characters to Hide Text within Text - Muntaha Abood Jassim (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study investigates a unique method of using invisible characters in text to conceal critical information from view. The idea of steganography has been thoroughly researched in a number of fields, such as audio and picture processing. But in recent years, there hasn’t been much focus on using invisible characters in text-based steganography. In order to hide content within plain text, our method makes advantage of the Unicode character set, which has a variety of invisible characters. We provide a steganography technique that conceals sensitive information in a way that is invisible to the human eye by embedding secret text into a cover text using a mix of invisible letters and zero-width gaps. Because it makes it possible to transmit dangerous information through seemingly innocent language without raising suspicions, this technique has important ramifications for secure communication. Additionally, our solution may be used with current encryption techniques to give sensitive data an extra degree of protection.